Indonesian EFL Learners’ Reading Motivation - Indrayadi, Toni (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2021)
Motivation in reading is very important for engaging learners in reading activity which can affect better reading comprehension. However, without motivation in reading can affect the worst reading comprehension. Therefore, motivation in reading needs to be constructed first by the teachers. This study examined whether intrinsic and extrinsic reading motivation different among students and reading motivation in general. This study used a descriptive quantitative approach with a survey design. Eighty-five third-year students voluntarily returned the motivation reading questionnaire about their motivation in reading. The data were analyzed through descriptive statistics using SPSS 23 and criteria-referenced and norm-referenced interpretations. From the analysis, it was found that most extrinsic reading motivation dimension percentages were slightly higher than intrinsic motivation and reading motivation dimension percentages in general in high category percentage. This study concludes that the external reason likely influenced students' motivation in reading. The students who were more motivated to read in this study were because of the expectation to get appreciation from others, good grades, better information from the text, and to finish the assignment. It also implies the theory of motivating students to engage with English reading texts.